Pengaruh e-service quality terhadap custome loyalty dengan customer trust sebagai variabel mediasi - Wulan Dia Nopita Sari; Rose Rahmidani (Universitas Negeri Surabaya, 2025)
This study aims to analyze the influence of e-service quality and e-word of mouth on customer loyalty with customer trust as a mediating variable on ShopeeFood service users in Padang City. The population in this study were Padang City residents who had used ShopeeFood services twice, with a sample size of 100 respondents selected through a purposive sampling technique. Data analysis was carried out using the Structural Equation Modeling method with the Partial Least Square (SEM-PLS) version 4.0 approach. The results of the analysis show that e-service quality, e-word of mouth, and customer trust have a positive and significant influence on customer loyalty. Furthermore, e-service quality and e-word of mouth have a positive and significant influence on customer trust. E-service quality has a positive and significant influence on customer loyalty through customer trust as a mediating variable. Meanwhile, e-word of mouth has a positive and significant influence on customer loyalty through customer trust as a mediating variable.